2016
DOI: 10.1161/strokeaha.115.011788
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Status on Baseline Computed Tomographic Angiography and Intra-Arterial Treatment Effect in Patients With Proximal Anterior Circulation Stroke

Abstract: Background and Purpose— Recent randomized trials have proven the benefit of intra-arterial treatment (IAT) with retrievable stents in acute ischemic stroke. Patients with poor or absent collaterals (preexistent anastomoses to maintain blood flow in case of a primary vessel occlusion) may gain less clinical benefit from IAT. In this post hoc analysis, we aimed to assess whether the effect of IAT was modified by collateral status on baseline computed tomographic angiography in the Multicenter Randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
180
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(209 citation statements)
references
References 30 publications
11
180
0
5
Order By: Relevance
“…They showed that patients with poor collaterals were four times more likely to clinically deteriorate in hospital as those with normal or exuberant collaterals. Other groups have also shown a relationship between collateral status and functional outcome20–22 with the recent post hoc analysis of the MR CLEAN data showing a significant modification of treatment effect by collateral status with the strongest benefit seen in patients with good collaterals (grade 3) and no effect seen in patients with absent collaterals (grade 0) 23. Our findings are consistent with previous reports with ∼70% of patients having good leptomeningeal collaterals.…”
Section: Discussionsupporting
confidence: 91%
“…They showed that patients with poor collaterals were four times more likely to clinically deteriorate in hospital as those with normal or exuberant collaterals. Other groups have also shown a relationship between collateral status and functional outcome20–22 with the recent post hoc analysis of the MR CLEAN data showing a significant modification of treatment effect by collateral status with the strongest benefit seen in patients with good collaterals (grade 3) and no effect seen in patients with absent collaterals (grade 0) 23. Our findings are consistent with previous reports with ∼70% of patients having good leptomeningeal collaterals.…”
Section: Discussionsupporting
confidence: 91%
“…However, our recanalization rates and outcomes are similar to the report of Sheth et al [6] that shows a successful recanalization in 87% of females versus 83% of males and functional independence at 3 months in 53% of females versus 56% of males. Besides, in our analysis, we included neither the collateral status nor the infarct volume, which are known outcome predictors [16,17]. Our study may be underpowered to detect sex differences (145 vs. 233 patients in the MR CLEAN trial [7]), but this is probably not the case, since the abovementioned cohort of 400 patients showed results overlapping with ours [6].…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 We also tested for a confounding effect of time from onset to start intra-arterial treatment and general anesthesia because these parameters are known to affect outcome. 12,13 Finally, we tested for confounding by center.…”
Section: Discussionmentioning
confidence: 99%